Fatal acute respiratory distress syndrome with diffuse alveolar damage: donor lymphocyte infusion imputability?. Issue 6 (1st September 2016) - Saillard, Colombe; Bisbal, Magali; Sannini, Antoine; Chow-Chine, Laurent; Brun, Jean-Paul; Harbi, Samia; Furst, Sabine; Blaise, Didier; Paciencia, Maria; Secq, Véronique; Mokart, Djamel
Donor lymphocyte infusion (DLI) is increasingly used after allogeneic haematopoietic stem cell transplantation (allo-HSCT), as a pre-emptive or curative immunotherapy of relapsed haematological malignancies, enhancing graft- versus -tumour effects [1]. The main complication is graft- versus -host disease (GVHD), with cumulative incidences of 40–60% and 33–61% for acute and chronic GVHD, respectively, typically developing 32–42 days after DLI [2]. Pulmonary complications after DLI are poorly documented. To our knowledge, there are no cases of diffuse alveolar damage (DAD) [3] after DLI in the literature to date. Here, we report our experience of two cases of acute respiratory distress syndrome (ARDS) with DAD following DLI after allo-HSCT, rapidly extending to fatal pulmonary fibrosis. Submission was approved by our institutional review board and informed consent was obtained. Fatal ARDS with diffuse alveolar damage: donor lymphocyte infusion imputability? http://ow.ly/WhxP3034P6s